Access Management for Digital Repository - Hossain Shoeb, Md. Zahid (DESIDOC Journal of Library & Information Technology, 2010)
Access management illustrates the process of providing controlled, and secure access to resources. It involves both authentication—the process of determining the validity of a user who claims to be, and autorisation—the process of determining what resources a user is permitted to access. Access management is significant as an important as well as one of the key services for the network infrastructure of digital repository activities for a wide range of audiences. Like the digital collection of digital repository, it also requires that the content be accessed and distributed as widely as possible to valid users around the globe. Access management and control is one of the major concerns for digital content authority over the Internet. Confidentiality and integrity of information cannot be ensured without a proper access management mechanism. Though most of the Institutional Repositories or Open Access Repositories are satisfied with the current mechanisms of the Open Source Software, which they use to build the repositories, restricted repositories or digital libraries demand more security and authenticity. The paper discusses the current practices and issues of access management for digital repositories including user authentications, user authorisation, authentication, and the technology of secured digital communication of digital materials. This paper also gives a basic idea about access management practices in Bangladesh by the digital content providers. http://dx.doi.org/10.14429/djlit.29.257